Pediatric Hemodialysis - Heeyeon Cho (Korean Society of Pediatric Nephrology, 2020)
Hemodialysis is rarely used in neonates and infants due to the risk of major complications in the very young. Nevertheless, there are clinical situations where hemodialysis is needed and may be helpful in small children. Recently, new developments in specialized hemodialysis equipment and specifically trained personnel have made it possible to implement hemodialysis in neonates and infants. In this review, we will discuss hemodialysis for the treatment of small children with renal replacement therapy-requiring conditions, and consider indications, prescriptions, complications, and ethical issues.